LEXICALIZACIÓN DE SECUENCIAS NOMBRE DEVERBAL-ADJETIVO RELACIONAL - Kornfeld, Laura; Resnik, Gabriela (Organon, 2012)
The present article focuses on the study of deverbal noun-relational adjective sequences suchas contaminación hídrica or gasto ambiental.. First, we characterise the properties of the relationaladjectives and the deverbal nouns that form the sequences and we distinguish two types of sequences,according to the distinction of Bosque & Picallo (1996) between thematic and classificatory relationaladjectives. From this classification, we revise the phenomenon of reduction (cf. Adelstein & Kuguel,1998). Finally, we propose possible terminographic applications of the above analysis.